EFEKTIVITAS ALZHEIMER’S DISEASE INTERNATIONAL DALAM MENANGANI MASALAH DEMENSIA DI CINA - Nanda Lusia Putri; Yusnarida Eka Nizmi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research is analyzing about effectiveness of Alzheimer’s Disease International which is an international organization that regulate dementia issues, dementia development issues in a country, Alzheimer’s Disease International cooperation with local authorities, diplomacy Alzheimer’s Disease International with local authorities to obtain permission to intervene the problem of dementia. Sources of funding, experience and policies which form the basis to suppress the growth of dementia in a country. This paper will describe in more detail of Alzheimer’s Disease International and China’s cooperation in tackling the problem of dementia, local government policy issues related to dementia, This study uses a pluralist perspective, which perspective is more emphasis on international cooperation between two independent actors that of cooperation that gave birth to an enlightenment in reducing the development of dementia in China. Alzheimer’s Disease International successful cooperation with China seen from the success of the conference to the 28th ADI in Taipei, China.Key Words: Dementia, IGO, Role, Conference, Diplomacy, China, Implementation